Selmân-I Pâk Fütüvvet-Nâmesi - Torun, Ali (Afyon Kocatepe Üniversitesi, 2000)
Tam metnini vermeyi düşündüğümüz Selmân-ı Pâk Fütüvvet- nâmesi Ankara Dil Tarih Coğrafya Fakültesi Kütüphanesi İsmail Saib I Bl. 2883 numarada kayıtlı olup 35 yapraktır. Eser, Dellâk, Natır, Külhan gibi hamam hizmeti gören esnafla berber, sünnetçi gibi tıraş ehli esnaf hakkındadır. Eser, yalnızca bir esnafa yönelik olarak düzenlenmesi bakımından önemlidir. Metin üç bölüm, konu ile alakalı soru ve cevaplardan oluşmaktadır.

The full text of “Selmân-ı Pak Fütüvvet-nâmesi” that we want to handle, is registered in the Library of Ankara University, Faculty of Language, History and Geography with the author İsmail Saib-I and numbered 2883 and consist of 35 sheets. This text is about the trades who deals with barbery like barbers, circumciser and Turkish bath service like Dellâk, Natır, Külhan (bath attendants who are in the service of massage, cleaning... ). The importance of this work is mainly related to its limited and intensive interest in only one branch of business. The text contains three chapters and some questions and answers related to the subject.
Keywords: Selmân-ı Pâk; Fütüvvet-nâme; Esnaf